2016
DOI: 10.1016/j.yhbeh.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin-33, but not cholecystokinin-8 shows gastrointestinal site specificity in regulating feeding behaviors in male rats

Abstract: Two separate experiments were performed to localize the gastrointestinal sites of action regulating meal size (MS), intermeal interval (IMI) length and satiety ratio (SR, IMI/MS) by cholecystokinin (CCK) 8 and 33. Experiment 1: CCK-8 (0, 0.05, 0.15, 0.25 nmol/kg) was infused in the celiac artery (CA, supplies stomach and upper duodenum) or the cranial mesenteric artery (CMA, supplies small and part of the large intestine) prior to the onset of the dark cycle in free feeding, male Sprague Dawley rats and MS (no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Further studies are required to determine the specific peripheral site of action that regulates reduction of food intake by NS CCK-8. For example, through intra-arterial infusions of various gut satiety peptides our laboratory demonstrated that the gastrointestinal tract contains sites of action regulating food intake reduction by S CCK-8, sulfated CCK-58, glucagon like peptide-1 and gastrin releasing peptide-29 (Sayegh et al, 2015;Williams et al, 2016;Washington et al, 2016;Washington et al, 2014). Similar experiments are needed to demonstrate a peripheral site of action regulating reduction of food intake by NS CCK-8.…”
Section: Discussionmentioning
confidence: 97%
“…Further studies are required to determine the specific peripheral site of action that regulates reduction of food intake by NS CCK-8. For example, through intra-arterial infusions of various gut satiety peptides our laboratory demonstrated that the gastrointestinal tract contains sites of action regulating food intake reduction by S CCK-8, sulfated CCK-58, glucagon like peptide-1 and gastrin releasing peptide-29 (Sayegh et al, 2015;Williams et al, 2016;Washington et al, 2016;Washington et al, 2014). Similar experiments are needed to demonstrate a peripheral site of action regulating reduction of food intake by NS CCK-8.…”
Section: Discussionmentioning
confidence: 97%
“…For example, while CCK-8, the most abundantly utilized form, reduced meal size when given exogenously (at various nmol/kg doses), CCK-58, the major endocrine form in rats and humans, reduced meal size and increased the interval time between meals 161 . Furthermore, the effects of the various forms of CCK, namely, CCK-8, 33, and 58, differ depending on their site of action in the gastrointestinal tract [162][163][164] . However, in studies, the most frequently administered exogenous form is CCK-8 165 , despite it not being the major endocrine form.…”
Section: Cckmentioning
confidence: 99%